2005
DOI: 10.1542/peds.2004-2387
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Adverse Events in Infants Hospitalized With Bronchiolitis

Abstract: Preventable AEs occur frequently among patients admitted for bronchiolitis, especially those who are critically ill. CIPs who suffer AEs during their hospitalization have longer hospital LOSs. Future studies should investigate error-prevention strategies with a focus on those patients with severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…One study of hospitalized children with bronchiolitis, for example, noted a 10% adverse error or near-miss rate for harm-causing interventions. 103 There are no studies on the effect of short-term, brief periods of hypoxemia such as may be seen in bronchiolitis. Transient hypoxemia is common in healthy infants.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…One study of hospitalized children with bronchiolitis, for example, noted a 10% adverse error or near-miss rate for harm-causing interventions. 103 There are no studies on the effect of short-term, brief periods of hypoxemia such as may be seen in bronchiolitis. Transient hypoxemia is common in healthy infants.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…(11, 12, 41, 42) A reduction in duration of hospitalization can bring important benefits not only for patients but also for healthcare facilities, as it decreases the risk of nosocomial infections, the likelihood of medical errors and hospital costs, and allows a more efficient bed turnover. (43) In addition to these objective outcomes, others not so easy to measure but important potential benefits of a timely discharge, include reestablishing the infant’s and family routine, which in turn may help patient recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of children admitted for bronchiolitis found that adverse events while in hospital occur in as many as 10 per 100 admissions. 35 These adverse events ranged from simple IV infiltrates to hospital acquired infections such as urinary tract infections or gastroenteritis, even in patients who were classified as "non-critically ill."…”
Section: Overdiagnosis and Harmmentioning
confidence: 99%